Investigation of the Yb and W Isotopic Chains using the Confined β-Soft Rotor Model - Papadopoulos, Dimitrios; Mertzimekis, Theodoros; Koseoglou, Pavlos; Bonatsos, Dennis; Vasileiou, Polytimos; Efstathiou, Margarita (HNPS Advances in Nuclear Physics, 2026)
The Confined β-soft (CBS) rotor model provides a simple collective approach in the region between the spherical vibrator and the axially deformed rotor limit for axially symmetric prolate (γ≈0) shapes. Even-even isotopes of Ytterbium and Tungsten serve as a good testing ground for exploring fundamental aspects of nuclear structure, as their R4/2=E(4+)/E(2+) ratio lies between 2.9 and 3.333. In the present study, the CBS formalism is applied to calculate the energies of the ground-state band, the associated B(E2) transition rates and the β-band excitations, directly comparing these predictions to available experimental data. The results demonstrate that CBS succeeds in reproducing the observed spectra and transition strengths for the case of axially symmetric isotopes of Yb and W.